African public sector financial managers – heroes or villains? – the origins and future prospects for public financial management reform in Sub-Saharan Africa. (1st January 2011) - Wynne, Andy
Contrary to the currently dominant view, it was not poor governance nor the associated corruption which were the prime causes of the development of poor public sector financial management in Sub-Saharan Africa. It was the economic problems across Sub-Saharan Africa, especially in the late 1970s and early 1980s, which led to a decline in the quality of public sector financial management and governance. The economic problems primarily arose from external events over which African governments had little or no control. Public sector financial managers across Sub-Saharan Africa, far from being the cause of the decline in the quality of public financial management, could be considered heroes and should be recognised as the key experts on the history, capabilities and short-comings of the systems they manage. As such, they should lead incremental reform programmes to re-build their systems rather than attempts at comprehensive and complex reforms effectively led by foreign consultants and the international financial institutions.